PENGEMBANGAN SISTEM PENCARIAN INFORMASI PADA HADIST RIWAYAT BUKHARI - jaka purnama sidi; dwi sakethi; Bambang Hermanto (Universitas Lampung, 2016)
Hadiths narrated by Bukhari hadith is no question of their validity in the level of Indonesian society. Because people are Muslims desperately need information fast hadith related by Bukhari. In the life of more advanced, more and more people find information that was not relevant in the spread of hadith Bukhari. To know the hadith infromasi, in accordance with the original or not, the communities need to open the book so thick and takes a long time. In order to accelerate and facilitate the public in Bukhari hadith access to the daily life of the days of the search information systems developed in the hadith narrated by Bukhari.In this study designed a web-based information system called Information Systems Development Search Hadith Bukhari, designed using programming languages PHP MySQL. With this information system, it is expected to answer the problems that occur in the community to access the hadith is easy with a relatively short time.Keywords: Hadith Bukhari, PHP MySQL, information systems